2014
DOI: 10.1089/pho.2013.3586
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy with 810 nm Wavelength Improves Skin Wound Healing in Rats with Streptozotocin-Induced Diabetes

Abstract: Objective: The aim of present study was to evaluate whether low-level laser therapy (LLLT) can reverse the impaired wound healing process in diabetic rats. Background data: Impaired wound healing in diabetic patients represents a major health problem. Recent studies have indicated that LLLT may improve wound healing in diabetic rats, but the optimal treatment parameters are still unknown. Materials and methods: Male SpragueDawley rats (n = 21) were randomly divided into three groups: a healthy control group, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…The PBM of 810 nm irradiation improve neurological performance in traumatic brain injury [16], accelerate both normal and chronic dermal wound healing [1720] and prevent the appearance of surgical scar [21]. Furthermore, 810 nm laser irradiation exhibited an anti-inflammatory effect on murine bone marrow derived dendritic cells that could be governed by cyclic adenosine monophosphate (cAMP) and reduced nuclear factor (NF)-kB signaling [22].…”
Section: Introductionmentioning
confidence: 99%
“…The PBM of 810 nm irradiation improve neurological performance in traumatic brain injury [16], accelerate both normal and chronic dermal wound healing [1720] and prevent the appearance of surgical scar [21]. Furthermore, 810 nm laser irradiation exhibited an anti-inflammatory effect on murine bone marrow derived dendritic cells that could be governed by cyclic adenosine monophosphate (cAMP) and reduced nuclear factor (NF)-kB signaling [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is a lack of studies that focus on the maturation and differentiation of the wounded epithelium after LLLT and throughout the healing process, although a study has demonstrated that the use of green LEDs increased the production of HB-EGF and VEGF [15], which do promote the migration of keratinocytes [16]. Most of the published literature is concerned with the clinical and morphological response of wound healing [17, 18] or the response of mesenchymal cells in either soft [19, 20] or hard tissues [21, 22] in tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro previous studies associated the low-level laser therapy to the modulation of cellular mechanisms such as DNA synthesis and gene expression [4,5], production of fibrotic cells [6], stimulation of cell proliferation [7][8][9], and cell differentiation [10][11][12][13], thus providing evidences to support a hypothesis of the implication of epigenetic mechanisms in the molecular responses that are evoked in the cells by the exposure to light sources [14].…”
Section: Introductionmentioning
confidence: 89%